Factors influencing pacing in triathlon - Wu SSX; Peiffer JJ; Brisswalter J; Nosaka K; Abbiss CR (Dove Medical Press, 2014)
Sam SX Wu,1 Jeremiah J Peiffer,2 Jeanick Brisswalter,3 Kazunori Nosaka,1 Chris R Abbiss1 1Centre for Exercise and Sports Science Research, School of Exercise and Health Sciences, Edith Cowan University, Perth, WA, Australia; 2School of Psychology and Exercise Science, Murdoch University, Perth, WA, Australia; 3Laboratory of Human Motricity, Education Sport and Health, University of Nice Sophia Antipolis, Nice, France Abstract: Triathlon is a multisport event consisting of sequential swim, cycle, and run disciplines performed over a variety of distances. This complex and unique sport requires athletes to appropriately distribute their speed or energy expenditure (ie, pacing) within each discipline as well as over the entire event. As with most physical activity, the regulation of pacing in triathlon may be influenced by a multitude of intrinsic and extrinsic factors. The majority of current research focuses mainly on the Olympic distance, whilst much less literature is available on other triathlon distances such as the sprint, half-Ironman, and Ironman distances. Furthermore, little is understood regarding the specific physiological, environmental, and interdisciplinary effects on pacing. Therefore, this article discusses the pacing strategies observed in triathlon across different distances, and elucidates the possible factors influencing pacing within the three specific disciplines of a triathlon. Keywords: cycle, endurance, multisport, pacing strategy, run, swim